The correlation between anxiety and depression levels with bulimic symptomatology and body mass index during COVID-19 quarantine measures: A 2-month follow-up study - Erdoğan Kaya, Ayşe; Turan, Çağlar; Oğur, Yavuz Selim; Yavaş, Nurullah; Erol, Atila (The European Research Journal, 2025)
Objective: This study aims to investigate the relationship between anxiety and depression levels with bulimia symptoms and body mass index (BMI) during the quarantine measures. Methods: Voluntary individuals were included, and individuals were evaluated before and after 2-month quarantine period, and self-report questionnaires were administered. In addition to the sociodemographic data form, Hospital Anxiety and Depression Scale (HADS) and Bulimic Investigatory Test, Edinburgh (BITE) were applied twice to the participants and their BMI were recorded. Results: An increase in HADS-A scores was observed after quarantine (z=-6.456, P<0.001). Upon comparing the scale scores, and BMI values recorded at the onset of the quarantine period and two months later, a negative correlation was observed between the BITE-2 (after 2-month follow-up) score and both the BMI-2 value and the HADS-A1 (baseline measurement) score, with correlation coefficients of r =-0.493, P<0.001, and r =-0.267, P=0.041, respectively. Additionally, BMI-1 values were positively correlated with HADS-D1 (r=0.186, P=0.028) and negatively correlated with BITE-1 score (r=-0.323, P<0.001). Conclusions: The finding of higher BMI in individuals with high depressive symptom severity, the negative correlation of bulimic symptoms with BMI, and higher anxiety levels after quarantine period reveal the impact of mental health on eating behavior and effect of pandemic on psychiatric symptoms. Our study can provide a unique perspective on eating behaviors and psychiatric symptomatology due to quarantine measures.